Beyond community engagement: centering research through Indigenous epistemologies and peoplehood. (September 2019) - Sumida Huaman, Elizabeth; Mataira, Peter
Indigenous research as discourse and practice has challenged researchers worldwide to foreground our work with clear attention to knowledge hierarchies and power inequities, ontologies and epistemologies, and critical ethical considerations. Yet, in the recent decade, it is not the rise of Indigenous research agendas but community-engaged scholarship that has been the focus of institutionalization at universities in the USA and elsewhere. In this commentary, we revisit Indigenous research and its political and liberatory agenda and offer a re-centering of research through peoplehood that is founded in Indigenous connections to place, cultural practices, and social justice work.